2016
DOI: 10.7150/thno.14064
|View full text |Cite
|
Sign up to set email alerts
|

Designing 3D Mesenchymal Stem Cell Sheets Merging Magnetic and Fluorescent Features: When Cell Sheet Technology Meets Image-Guided Cell Therapy

Abstract: Cell sheet technology opens new perspectives in tissue regeneration therapy by providing readily implantable, scaffold-free 3D tissue constructs. Many studies have focused on the therapeutic effects of cell sheet implantation while relatively little attention has concerned the fate of the implanted cells in vivo. The aim of the present study was to track longitudinally the cells implanted in the cell sheets in vivo in target tissues. To this end we (i) endowed bone marrow-derived mesenchymal stem cells (BMMSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Recent studies showed that the ECM secreted by MSCs could be the bridge to connect the cells and it can make MSCs easier to stay in place where they need to function. In addition, they can create the microenvironment to maintain homeostasis and they also can enhance the survival capacity of MSCs effectively [ 62 , 63 ]. Meanwhile, the decellularized ECM mainly focuses on the recruitment of endogenous stem cells and immune cells to rebuild the destroyed microenvironment [ 33 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the ECM secreted by MSCs could be the bridge to connect the cells and it can make MSCs easier to stay in place where they need to function. In addition, they can create the microenvironment to maintain homeostasis and they also can enhance the survival capacity of MSCs effectively [ 62 , 63 ]. Meanwhile, the decellularized ECM mainly focuses on the recruitment of endogenous stem cells and immune cells to rebuild the destroyed microenvironment [ 33 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the last two decades, cell sheets of MSCs have been used in tissue engineering/tissue regeneration of several types of tissues and/or organs including (but are not limited to) the cornea [ 39 ], skin [ 40 , 41 ], cartilage [ 42 , 43 ], meniscus [ 44 ], bone [ 31 , 45 53 ], tendons [ 53 ], cardiac tissue [ 54 – 62 ], periodontal tissue [ 63 , 64 ], nasal epithelium [ 65 ], tooth [ 66 ], and blood vessel [ 67 ]. Cell sheets of MSCs have also been used in conditions such as wound healing [ 41 ], oral ulcers [ 68 ], digestive fistula [ 69 ], and spinal cord defects [ 70 , 71 ]. It has also been demonstrated that MSC sheets can induce angiogenesis in ischemic and/or wound tissues [ 41 , 72 ].…”
Section: Mesenchymal Stem Cells and Their Use In Cell Sheet-based mentioning
confidence: 99%
“…Recent studies on exosomes [56] and Gabriel Rahmi’s latest study [57] revealed that although most of the implanted cells would die in a few days, they could be involved in tissue repair through the paracrine effect, which offer us some insights regarding future investigations. In addition, clinical periodontal tissue defects normally are accompanied by inflammation, whether the composite can properly function in this microenvironment remains unknown.…”
Section: Discussionmentioning
confidence: 99%